Identification of a novel boronic acid as a potent, selective, and orally active hormone sensitive lipase inhibitor. Issue 16 (15th August 2016) - Ogiyama, Tomoko; Yamaguchi, Mitsuhiro; Kurikawa, Nobuya; Honzumi, Shoko; Yamamoto, Yuka; Sugiyama, Daisuke; Inoue, Shinichi
Graphical abstract: Abstract: Hormone sensitive lipase (HSL) is an attractive therapeutic target of dyslipidemia. We designed and synthesized several compounds as reversible HSL inhibitors with a focus on hydrophobic interactions, which was thought to be effective upon the HSL inhibitory activity. In these efforts, we identified boronated compound12 showing a potent HSL inhibitory activity with an IC50 value of 7 nM and a high selectivity against cholinesterases. Furthermore, compound12 is the first boron containing HSL inhibitor that has shown an antilipolytic effect in rats after oral administration at 3 mg/kg.